Inquiry-based learning, the nature of science, and computer technology: New possibilities in science education - John P Kubieck (The Canadian Network for Innovation in Education (CNIE), 2005)
The teaching of science in the K-12 classroom has been less than successful. Students typically do not develop science literacy and do not understand the role and relevance of science in society. Inquiry-based learning is an approach which promises to improve science teaching by engaging students in authentic investigations, thereby achieving a more realistic conception of scientific endeavour as well as providing a more learner-centred and motivating environment. It can also be used to support teaching the nature of science. The inquiry approach, while lauded by educators, is still not prevalent in the classroom, and is often misused. This may be the result of multiple factors, such as amount of classroom time, lack of effective means for students to conduct independent investigations, the difficulty of incorporating abstract concepts with inquiry, and lack of teacher expertise and experience. Computer technology has evolved now to the point where it can greatly facilitate the use of inquiry learning on many levels, and provide new tools for representing the nature of science in the classroom. This use of technology to support new teaching approaches and objectives holds great promise for improving science education in the classroom, as long as the inherent limitations are recognized and technology is used as a tool rather than as a foundation.